The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1525-1594.1996.tb04541.x
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Vacuum‐Powered Blood‐Pumping Device with Active Valves

Abstract: We propose a new vacuum-driven blood pump having a tubular shape with active valves. This design avoids any possible problems caused by membrane breakage, thereby minimizing the risk of gas embolic events and stagnation regions. By using active valves, it is possible to ensure better flow control and minimize pressure gradients inside and outside the pump. The low cost of the pump's disposable parts enables it to be used for such applications as a ventricular assist device, a pulsatile pump device in extracorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…However, pulsatile pumps have not yet been used for continuous venovenous renal replacement therapy in humans. Our group has designed a new, easy-tohandle, vacuum-driven, tubular, blood pumping device that can be used with a wide range of blood flows [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pulsatile pumps have not yet been used for continuous venovenous renal replacement therapy in humans. Our group has designed a new, easy-tohandle, vacuum-driven, tubular, blood pumping device that can be used with a wide range of blood flows [11].…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, roller pumps automatically increase the pressure, within certain limits, to maintain the same blood flow. However, the pulsatile pump does not autoregulate the pressure and, when resistance develops in the circuit, the blood flow decreases [11]. For this reason, it is important to use very sensitive flow sensor systems and alarms to allow the physician to modify the pressure and/or frequency of pulsation according to the changes in blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pulsatile pump designed and patented by the Community of Madrid (Spain) was used (9). The characteristics of this pump have been described previously (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…However, pulsatile pumps have still not been used for CRRT in clinical practice. Our group has designed a pulsatile tubular pump that has demonstrated its efficacy in experimental models as a pump for CRRT (9)(10)(11). In a previous study with a prototype of the pump, we demonstrated that the ultrafiltrate flow increases with increasing catheter diameter, BF, pump frequency, and diastolic time (11).…”
mentioning
confidence: 95%